2018
DOI: 10.1161/cir.0000000000000569
|View full text |Cite
|
Sign up to set email alerts
|

Low-Calorie Sweetened Beverages and Cardiometabolic Health: A Science Advisory From the American Heart Association

Abstract: In the United States, 32% of beverages consumed by adults and 19% of beverages consumed by children in 2007 to 2010 contained low-calorie sweeteners (LCSs). Among all foods and beverages containing LCSs, beverages represent the largest proportion of LCS consumption worldwide. The term LCS includes the 6 high-intensity sweeteners currently approved by the US Food and Drug Administration and 2 additional high-intensity sweeteners for which the US Food and Drug Administration has issued no objection letters. Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 59 publications
1
89
0
2
Order By: Relevance
“…These contradictory results can possibly be attributed to differences in inclusion criteria, statistical methods, and adjustments used by different authors. Additionally, a review by Romo‐Romo et al, 39 which synthesized results from prospective cohort studies evaluating cardiometabolic outcomes, found that associations between NNS consumption and both obesity and metabolic diseases are attenuated when analyses include adjustments for confounding variables related to adiposity and also addressed the possibility of inverse causality 40 . Our meta‐analysis, composed exclusively of RCTs, showed overall weight reduction when NNS were used as an intervention.…”
Section: Discussionmentioning
confidence: 66%
“…These contradictory results can possibly be attributed to differences in inclusion criteria, statistical methods, and adjustments used by different authors. Additionally, a review by Romo‐Romo et al, 39 which synthesized results from prospective cohort studies evaluating cardiometabolic outcomes, found that associations between NNS consumption and both obesity and metabolic diseases are attenuated when analyses include adjustments for confounding variables related to adiposity and also addressed the possibility of inverse causality 40 . Our meta‐analysis, composed exclusively of RCTs, showed overall weight reduction when NNS were used as an intervention.…”
Section: Discussionmentioning
confidence: 66%
“…A recent American Heart Association science advisory concluded that “at this time, it is prudent to advise against prolonged consumption of LCSB by children.” The authors further stated that “the use of other alternatives to sugar‐sweetened beverages, with a focus on water, should be encouraged.” Our results support this recommendation, as while cross‐sectional analyses cannot establish causality, LCSB consumption was associated with both higher energy intake and higher sugar intake in comparison with water, with energy intakes among LCSB consumers similar to SB consumers. Given that the highest intakes of energy, carbohydrates, and sugar were observed among combined consumers of LCSB + SB, these results suggest that LCSB may be used in addition to, rather than as a replacement for, SBs in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Most report positive associations between NSS intake (mostly from diet beverages), weight gain, and risk of cardiometabolic diseases 1. However, inherent biases such as residual confounding by related diet and lifestyle factors or reverse causation (whereby individuals use NSS as a strategy to control their weight or metabolic risk) complicate the interpretation of the results 1…”
mentioning
confidence: 99%